The Influence of Concept Map Learning Strategies and Thinking Styles on Cultural History Islamic Students Madrasah Ibtidaiyah in Private - Tanjung, Rahmad Mulyadin; Zein, Achyar; Budianti, Yusnaili (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to determine the impact of the concept map learning strategy and thinking style on the learning outcomes of Islamic Cultural History for students at Gunungsitoli City's Private Madrasah Ibtidaiyah. This study employs an experimental method with a 2 x 2 quasi-experimental factorial design. The influence of concept mapping and expository learning strategies on learning outcomes of Islamic Cultural History in terms of students' thinking styles will be compared using this design. According to the findings of this study, students from the Gunungsitoli Private Madrasah in Gunungsitoli who were taught using concept map learning strategies achieved higher Islamic Cultural History learning outcomes than students who were taught using expository learning strategies, where the average value of history learning outcomes was lower. Students at Private Madrasah Ibtidaiyah in Gunungsitoli City who were taught with the concept map learning strategy had a higher level of Islamic culture than students who were taught with the expository learning strategy.